Heme oxygenase-1 is critically involved in placentation, spiral artery remodeling, and blood pressure regulation during murine pregnancy - Zenclussen, Maria L.; Linzke, Nadja; Schumacher, Anne; Fest, Stefan; Meyer, Nicole; Casalis, Pablo A.; Zenclussen, Ana C. (Frontiers in Pharmacology, 2015)
The onset of pregnancy implies the appearance of a new organ, the placenta. One main function of the placenta is to supply oxygen to the fetus via hemoproteins. In this review, we highlight the importance of the enzyme heme oxygenase-1 (HO-1) for pregnancy to be established and maintained. HO-1 expression is pivotal to promote placental function and fetal development, thus determining the success of pregnancy. The deletion of the gene Hmox1 in mice leads to inadequate remodeling of spiral arteries and suboptimal placentation followed by intrauterine growth restriction (IUGR) and fetal lethality. A partial Hmox1 deletion leads to IUGR as well, with heterozygote and wild-type fetuses being born, but Hmox1–/– significantly below the expected Mendelian rate. This strong phenotype is associated with diminished number of pregnancy-protective uterine natural killer (uNK) cells. Pregnant heterozygote females develop gestational hypertension. The protective HO-1 effects on placentation and fetal growth can be mimicked by the exogenous administration of carbon monoxide (CO), a product of heme catalyzed by HO-1. CO application promotes the in situ proliferation of uNK cells, restores placentation and fetal growth, while normalizing blood pressure. Similarly, HO-1 inhibition provokes hypertension in pregnant rats. The HO-1/CO axis plays a pivotal role in sustaining pregnancy and aids in the understanding of the biology of pregnancy and reveals a promising therapeutic application in the treatment of pregnancy complications.